The effect of irrigating solutions on the hydration of tricalcium silicate cements: an in vitro study - Shivani Shreya, K; Deepthi, G.; Khwaja Moinuddin, Md; Pallavi, R; Asha, Reddy; Amulya, Reddy (International Journal of Dental Materials, 2023)
Background: Calcium silicate cements are hydraulic cements, routinely used for perforation repairs. During such repairs, these cements are invariably exposed to irrigating solutions. Aim: This study aimed to understand the effect of irrigating solutions on the hydration of calcium silicate cements. Materials and Methods: Sixty extracted teeth were taken and horizontal sections of 2mm were obtained. These samples were randomly divided into two groups viz. Biodentine and BioMTA Plus groups later these cements were condensed into the canal spaces and allowed to set until their setting time. These samples were further subdivided and allowed to encounter three irrigating solutions viz. Normal saline, 17% EDTA, and 2% Chlorhexidine for 5 minutes. These were allowed to mature in an incubator for seven days and subjected to Scanning Electron Microscopy and Energy Dispersive X-ray analysis. Results: The SEM analysis of the Biodentine/control group displayed a petal-like appearance, with a Ca/Si ratio of 2. Whereas, the Biodentine/Normal saline, Biodentine/17% EDTA and Biodentine/2% Chlorhexidine group displayed crumbled paper-like appearance. The Ca/Si ratios for the Biodentine/Normal saline, Biodentine/17% EDTA and Biodentine/2% Chlorhexidine were 2.72, 1.6, and 4.21, respectively. In the BioMTA Plus group, all the SEM analyses displayed round crystalline structures in all groups. The Ca/Si ratio of BioMTA Plus/Control, BioMTA Plus/17% EDTA and BioMTA Plus/2% Chlorhexidine were 25.5, 17.42, 24.1, and 39.4, respectively. Conclusion: The study concluded that the irrigating solutions did not affect the hydration mechanism of Biodentine and BioMTA Plus despite the variations in the Ca/Si ratios and surface morphology.